Germline control of somatic Kras mutations in mouse lung tumors. Issue 6 (25th March 2018) - Borrego, Andrea; Cabrera, Wafa H.K.; Jensen, José R.; Correa, Mara; Ribeiro, Orlando G.; Starobinas, Nancy; De Franco, Marcelo; Pettinicchio, Angela; Dragani, Tommaso A.; Ibañez, Olga C.M.; Manenti, Giacomo
Abstract : Somatic KRAS mutations are common in human lung adenocarcinomas and are associated with worse prognosis. In mice, Kras is frequently mutated in both spontaneous and experimentally induced lung tumors, although the pattern of mutation varies among strains, suggesting that such mutations are not random events. We tested if the occurrence of Kras mutations is under genetic control in two mouse intercrosses. Codon 61 mutations were prevalent, but the patterns of nucleotide changes differed between the intercrosses. Whole genome analysis with SNPs in (A/J x C57BL/6)F4 mice revealed a significant linkage between a locus on chromosome 19 and 2 particular codon 61 variants (CTA and CGA). In (AIRmax × AIRmin) F2 mice, there was a significant linkage between SNPs located on distal chromosome 6 (around 135 Mbp) and the frequency of codon 61 mutation. These results reveal the presence of two loci, on chromosomes 6 and 19, that modulate Kras mutation frequency in different mouse intercrosses. These findings indicate that somatic mutation frequency and type are not simple random events, but are under genetic control.